Uma pronúncia standar das vogais nasais do português brasileiro - Santos, Vanessa Carrasco (2011)
This dissertation is situated in the area of Portuguese Language Description and limited aspects of nasal vowels articulation pre, post and tonic in Brazilian Portuguese. There has been concern in the quantitative and qualitative description of the standardized pronunciation, by TV Globo, the nasal vowels of Brazilian Portuguese. The aim of this work is to contribute to studies of identity of a standard pronunciation of Brazilian Portuguese, in order to provide the "desestrangeiração" students, speakers of other languages who are learning Brazilian Portuguese. It has specific goals for: 1 - The qualitative and quantitative description of the pronunciation of nasal vowels pre-stress; 2 - The qualitative and quantitative description of the pronunciation of nasal vowels post-tonic; 3 - The qualitative and quantitative description of the pronunciation of nasal vowels tonic; The procedure of analysis was descriptive and explanatory materials being collected in the database of pronunciation stander, file this one from Prof. Dr. Regina Celia Pagliuchi da Silveira. The results enabled the formulation of rules for the pronunciation of Brazilian Portuguese idiom: 1-The pre-stress nasal vowels are articulated following the control of the letter; 2-The vowels post-tonic is made by nasal vowel or the vowel reduction or desnasalação; 3-Vowels tonic is made by nasal vowels monotongações or ditongações, depending on the number of syllables in the word, The 4-ditongações preferably are increasing; We conclude that there is a standardized pronunciation for the nasal vowels of Brazilian Portuguese and this is controlled by phonological rules, phonetic and morfofonológicas